CATALYST-FREE SYNTHESIS OF SYNTHESIS OF BIOLOGICAL ACTIVE FUNCTIONALIZED QUINOLONES - Veerappan Jeyachandran (International Journal of Modern Agriculture, 2020)
Quinolones and fluoroquinolones are synthesized in the metal catalysed 2-methylquinoline 1a and benzaldehyde 2a were chosen as the model substrates and subjected to the reactions under the catalyst-free conditions (1). The reaction proceed at 140 0C